Criminal Liability of Participants in the Commission of the Crime of Fraud (A Study of Decision Number: 46/Pid.B/2021 PN MGG) - Try Romanto Wibisono (Green Publisher Indonesia, 2026)
Fraud is a criminal offense against property, primarily regulated under Article 378 of the Indonesian Criminal Code (KUHP). This crime may be committed jointly with others, known as participation. The criminal liability of each participant can vary based on their role and involvement. This study applies a normative legal research method using secondary data from literature studies, analyzed through qualitative descriptive analysis. Based on the findings in Decision No. 46/Pid.B/2021/PN Mgg, the defendants fulfilled the criteria of criminal responsibility (actus reus) by committing acts prohibited under Article 378 in conjunction with Article 55(1) to 1 of the Criminal Code, consistent with Hans Kelsen's theory of legal responsibility. Gustav Radbruch's theory of legal certainty further emphasizes that law must be both certain and fair, taking into account all relevant aspects of the case. The panel of judges found the defendants legally and convincingly guilty of jointly committing fraud. Consequently, sentences of one year and ten months, and one year and two months of imprisonment were imposed. The judge's considerations included legal grounds, trial facts, witness testimonies, evidence, judicial conviction, and applicable criminal sanctions.